How Sense of Community Affects Sense of Self Among Sexual Minorities: Critical Consciousness as a Mediating Mechanism. - Yip, Charles Chiu Hung; Chan, Kevin Ka Shing (American Journal of Community Psychology, 2021)
Research shows that sense of community may enable lesbian, gay, and bisexual (LGB) individuals to resist and fight against societal heterosexism and increase their positive sense of self. Less is known, however, about the underlying processes. The present study examined whether sense of community would affect sense of self (i.e., identity affirmation and self‐esteem) through critical consciousness (i.e., critical reflection and critical action) among LGB individuals. A total of 401 LGB individuals from Hong Kong, China, provided cross‐sectional questionnaire data on sense of community, critical reflection, critical action, identity affirmation, and self‐esteem. Structural equation modeling and bootstrap analyses were performed to analyze the direct and indirect relations among the variables. Results showed that sense of community was positively associated with critical action, and this association was mediated by critical reflection. Moreover, critical action was positively associated with self‐esteem, and this association was mediated by identity affirmation. Theoretically, this study demonstrated how LGB individuals' sense of community may have a positive impact on their sense of self through the mechanism of critical consciousness. Practically, this study pointed to the utility of cultivating positive in‐group perceptions among LGB individuals in liberating them from oppressive ideology, mobilizing them to resist social injustice, enhancing their identity affirmation, and increasing their self‐esteem. Highlights: The association between sense of community and sense of self is mediated by critical consciousness.Sense of community liberates LGB individuals from societal heterosexism.Sense of community mobilizes LGB individuals to join individual and collective advocacy actions.Critical consciousness has an identity‐affirming effect for LGB individuals.Critical consciousness has a self‐empowering effect for LGB individuals.